2019
DOI: 10.3390/jcm8091479
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Well-Differentiated Gastro-Entero-Pancreatic Tumors Are Associated with Metabolic Syndrome

Abstract: The association of well-differentiated gastro-entero-pancreatic neuroendocrine tumors (WD GEP-NETs) with metabolic syndrome (MetS), abdominal obesity, and fasting glucose abnormalities was recently described. The aim of this study was to evaluate whether the presence of MetS or any MetS individual component was also influenced by GEP-NET characteristics at diagnosis. A cohort of patients with WD GEP-NETs (n = 134), classified according to primary tumor location (gastrointestinal or pancreatic), pathological gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…Our group has recently described an association between MetS and some MetS individual components, such as visceral obesity and abnormal FPG with WD GEP-NEN [ 17 ]. We have also found that patients with WD GEP-NEN and MetS had a higher risk of presenting a lower tumor grade yet disseminated disease at diagnosis, independently of primary tumor site and hormonal status [ 27 ]. In support of our previous study’s findings, a metanalysis published by Leoncini et.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently described an association between MetS and some MetS individual components, such as visceral obesity and abnormal FPG with WD GEP-NEN [ 17 ]. We have also found that patients with WD GEP-NEN and MetS had a higher risk of presenting a lower tumor grade yet disseminated disease at diagnosis, independently of primary tumor site and hormonal status [ 27 ]. In support of our previous study’s findings, a metanalysis published by Leoncini et.…”
Section: Discussionmentioning
confidence: 99%
“…One group has previously observed an association between well‐differentiated GEP‐NETs and metabolic syndrome and visceral obesity. 17 , 18 Higher fasting glucose and glucose intolerance were described previously in two small samples of patients with NETs; however, the prevalence of DM diagnoses in the GEP‐NET population has not been studied. 17 , 25 It has been proposed that DM and neuroendocrine tumors share components in their pathogenesis, though the exact mechanism is not known.…”
Section: Discussionmentioning
confidence: 94%
“… 17 , 18 Higher fasting glucose and glucose intolerance were described previously in two small samples of patients with NETs; however, the prevalence of DM diagnoses in the GEP‐NET population has not been studied. 17 , 25 It has been proposed that DM and neuroendocrine tumors share components in their pathogenesis, though the exact mechanism is not known. 26 This is supported by studies showing that some medications for diabetes such as metformin have been associated with slower tumor progression in NET patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The prevalence and incidence of gastroenteropancreatic neuroendocrine tumors (GEP-NET) is increasing over the past 2 decades, partly due to the growing availability of advanced endoscopic and radiological imaging techniques in detecting more accurately benign and incidentally discovered lesions [ 9 ]. The complex clinical presentation and course of GEP-NET deserves special attention in early diagnosis and treatment, particularly in their association with metabolic consequences that represent risk determinants of well-differentiated GEP-NET, similarly to other types of cancers [ 10 ]. Thus, the management of patients with GEP-NET requires an integrated multidisciplinary approach, and nutrition is an essential component of the assessment and management of these patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%